2018
DOI: 10.1021/acsphotonics.8b00298
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Nanoantenna Arrays as Efficient Etendue Reducers for Optical Detection

Abstract: Optical detectors require the efficient collection of incident light onto a photodetector. Refractive or reflective optics are commonly used to increase the collected power. However, in the absence of losses, such optics conserve etendue and therefore pose a limit on the field of view and the active area of the detector. A promising method to overcome this limitation is to use an intermediate layer of fluorescent material that omnidirectionally absorbs the incident light and preferentially emits toward the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…The improvement of the quality factor relies on the enhanced radiative coupling of the individual nanoparticles, and as mentioned before, the modes that are formed through this condition are the SLRs. Arrays of optical antennas supporting SLRs can be regarded and the optical analog of antenna phased arrays that emit electromagnetic waves only in defined directions given by the relative phases of the individual antennas [60,61]. Some examples of such arrays are shown in the scanning electron microscope (SEM) images of Figs.…”
Section: Surface Lattice Resonancesmentioning
confidence: 99%
“…The improvement of the quality factor relies on the enhanced radiative coupling of the individual nanoparticles, and as mentioned before, the modes that are formed through this condition are the SLRs. Arrays of optical antennas supporting SLRs can be regarded and the optical analog of antenna phased arrays that emit electromagnetic waves only in defined directions given by the relative phases of the individual antennas [60,61]. Some examples of such arrays are shown in the scanning electron microscope (SEM) images of Figs.…”
Section: Surface Lattice Resonancesmentioning
confidence: 99%
“…To elucidate the effect of different dielectric substrates, we investigate additional WS 2 monolayers transferred to hydrophobic polystyrene, hydrophilic fused silica, and alumina/silica. We chose these substrates due to their extended use in nanophotonic applications . We plot the normalized time‐resolved PL decay measurements of monolayer WS 2 , obtained via FLIM, before and after soft‐transfer encapsulation in these dielectric substrates in Figure S3 (Supporting Information).…”
Section: Effect Of Changing Dielectric Environmentmentioning
confidence: 99%
“…They showed experimentally that this nano-patterned approach improved the optical gain of the antenna from 2.2 to 3.2. Wang et al [89] reported that arrays of metallic nanoparticles can act as étendue reducers. They have shown that an aluminium nanoparticle array can interact with dye molecules suspended in a polymer and change the angle distribution of the emission.…”
Section: Fluorescent Antennas For Visible Light Communicationsmentioning
confidence: 99%